Regional cooperation : a theoretical framework and application to the east ASEAN growth area - Lim, Bee Leng (2014)
The world is increasingly becoming more integrated. This is all too evident in the number of regional groupings that have sprung into existence since world war II and this trend is most manifest in the nineties. The hottest topic at the moment in East Asia is growth triangles - regions that are identified as having vast growth potential when they cooperate economically to achieve synergy and growth which, alone, they are unable to achieve.